Thrombus Degradation by Fibrinolytic Enzyme of Stenotrophomonas sp. Originated from Indonesian Soybean-Based Fermented Food on Wistar Rats - Florensia Nailufar; Raymond R. Tjandrawinata; Maggy T. Suhartono (Advances in Pharmacological Sciences)
Objective. To evaluate thrombus degrading effect of a fibrinolytic enzyme from food origin Stenotrophomonas sp. of Indonesia. Methods. Prior to animal study, the enzyme safety was tested using cell culture. The effect on expression of tissue plasminogen activator was also analysed in the cell culture. For in vivo studies, 25 Wistar rats were used: normal control, negative control, treatment groups with crude and semipurified enzyme given orally at 25 mg/kg, and positive control group which received Lumbrokinase at 25 mg/kg. Blood clot in the tail was induced by kappa carrageenan injection at 1 mg/kg BW. Results. Experiment with cell culture confirmed the enzyme safety at the concentration used and increased expression of tPA. Decreasing of thrombus was observed in the positive group down to 70.35 ± 23.11% of the negative control animals (100%). The thrombus observed in the crude enzyme treatment was down to 56.99 ± 15.95% and 71.5 ± 15.7% for semipurified enzyme. Scanning electron microscopy showed clearly that bood clots were found in the animals injected with kappa carrageenan; however, in the treatment and positive groups, the clot was much reduced. Conclusions. Oral treatment of enzyme from Stenotrophomonas sp. of Indonesian fermented food was capable of degrading thrombus induced in Wistar rats.